Associations of work characteristics with obesity, behavioral risk factors and NCDs in Bangkok, Thailand. - Sopit Nasueb; Hathairat Kosiyaporn; Nisachol Cetthakrikul; Rujira Adhibai; Jiranun Thiphong; Yanisa Pumsutas; Orratai Waleewong (PLOS Global Public Health)
Non-communicable diseases (NCDs) are one of the premature causes of death in Thailand especially among working age group. This study aims to examine the associations between work characteristics and NCDs, obesity, and behavioral risk factors in Bangkok, the Capital of Thailand. This study employed secondary data analysis of cross-sectional data from the Health Behavior of Population Survey 2021 by the National Statistical Office (NSO). The respondents who were 15-60 years old and resided in Bangkok were included in this study (n = 4,925). The data were analyzed by descriptive statistics of work characteristics, and multiple logistic regression between working groups and behavioral risks adjusted with other demographic and socioeconomic variables. The study found that all workers showed a lower likelihood of reporting NCDs compared to the unemployed. Professional/administrative/managerial workers had 44% less chances of reporting NCDs compared to unemployed (AOR = 0.56; 95%CI = 0.43-0.75; P-value <0.001. All working groups showed a significant association with alcohol consumption, smoking, and dietary intake. In particular, skilled, semi-skilled, unskilled workers, technicians, clerks, and service or sales workers were more likely to smoke and drink alcohol compared to those who were unemployed. Nevertheless, work characteristics did not affect the likelihood of inappropriate fruit and vegetable intake, insufficient physical activity, and sedentary behavior. The study found a link between work characteristics and NCDs in the working-age population, identifying specific work characteristics associated with behavioral risk factors such as alcohol consumption, smoking, and high dietary risk. The findings suggest a need for NCD prevention strategies targeting diverse workplaces such as smoking regulations, healthy canteens, and promoting opportunities for physical activity, with a regulatory focus on labor laws and policy incentives. Finally, disaggregated occupational data should be emphasis for effective monitoring and evaluation in NCD policy.